The Temporal-Spatial Scope in the Memoir “The Major Events of My Life” by Ghazaros Aghayan - TOROSYAN, ANNA (Bulletin of Yerevan University B: Philology, 2021)
In the article, we examine “The Major Events of My Life”, which is part of the memoir legacy of Ghazaros Aghayan. The memoir “The Major Events of My Life”, which covers the events of the 1850s up to the beginning of the 1890s, is not merely a collection of biographical facts, but a piece of writing which gives a comprehensive idea of the Armenian social life of the very period: it depicts Armenian cultural life based on historical documentary materials, revealing a number of events and individuals through different events.
Keywords: genre, portrait, environment, documentary, adventure episodes